The Impact of Contemporary Environmental Migrations on International Security - Staszkiewicz, Zofia (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The 20th and 21st century is a period of great changes, with the civilization-enhancing digital revolution on the one hand and the emergence of new global threats on the other hand. Unarguably, global warming is among the most serious challenges, bringing about dire consequences for humans, the environment and the international security. One of them is the phenomenon of contemporary environmental migrations, which was until recently marginalized, and today causes deep concerns of the entire international community. The purpose of this article is to characterize the problem of contemporary environmental migrations, present the predictions regarding its further development, and discuss its effects on the individuals affected, states and international relations.

Przełom XX i XXI wieku to wyjątkowy okres w historii cywilizacji, naznaczony rewolucją techniczną i cybernetyczną, ale także nowymi zagrożeniami i problemami. Niewątpliwie jednym z najpoważniejszych jest żywo dyskutowany efekt cieplarniany oraz jego skutki dla człowieka, środowiska naturalnego oraz bezpieczeństwa międzynarodowego. Problem współczesnych migracji klimatycznych, choć jeszcze niedawno bagatelizowany, dziś budzi niepokój społeczności międzynarodowej. Celem artykułu jest omówienie fenomenu współczesnych migracji klimatycznych, przedstawienie prognoz rozwoju problemu w najbliższych dziesięcioleciach oraz prześledzenie jego następstw dla osób bezpośrednio dotkniętych, państw i dla systemu stosunków międzynarodowych.
Wpływ współczesnych migracji klimatycznych na stosunki międzynarodowe